2010
DOI: 10.1007/s00468-010-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing canopy metrics derived from terrestrial and airborne laser scanning in a Douglas-fir dominated forest stand

Abstract: Accurate estimates of vegetation structure are important for a large number of applications including ecological modeling and carbon budgets. Light detection and ranging (LiDAR) measures the three-dimensional structure of vegetation using laser beams. Most LiDAR applications today rely on airborne platforms for data acquisitions, which typically record between 1 and 5 ''discrete'' returns for each outgoing laser pulse. Although airborne LiDAR allows sampling of canopy characteristics at stand and landscape lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 40 publications
(62 reference statements)
7
149
0
Order By: Relevance
“…TLS and ALS have been combined to estimate canopy structure at the plot level (Hilker et al 2010;Lovell et al 2003). In the present study, TLS and ALS are combined at tree level.…”
Section: Introductionmentioning
confidence: 99%
“…TLS and ALS have been combined to estimate canopy structure at the plot level (Hilker et al 2010;Lovell et al 2003). In the present study, TLS and ALS are combined at tree level.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of the results from egg shaped tree crown models also implies that the validation is not sensitive to the exact choice of crown models. To obtain detailed ground measurements of the tree crowns, terrestrial laser scanning is a promising technique which is currently being developed for this purpose (Hilker et al 2010;Hosoi et al 2010;Lovell et al 2003). Most of the field inventory was done less than one growth season after the laser scanning except for the measurement of live crown height which was done two growth seasons after the laser scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Harding et al (2001) estimated canopy height profiles for four selected forest stands from ALS data from SLICER using measurements from a telephoto lens calibrated to measure distances as ground truth. Hilker et al (2010) estimated canopy volume profiles for four forest stands from ALS point data and compared them with canopy volume profiles estimated from terrestrial laser scanning. Hosoi et al (2010) estimated Leaf Area Density (LAD) in a forest plot from ALS data and compared with LAD estimated from TLS data.…”
Section: Introductionmentioning
confidence: 99%
“…In this study TLS-based measurements were found more reliable than conventional field methods. Therefore, TLS data should be considered a suitable tool to validate crown radius measurement from airborne laser scanning (Hilker et al 2010, Hauglin et al 2014 and it may also be useful for comparisons with high spatial resolution abovecanopy imagery. On the long term, airborne approaches for crown radius measurements are likely to be more widely applied to forest areas and they will benefit from detailed ground truth data by means of TLS.…”
Section: Tree Growth and Crown Dimensions In Fagus Sylvaticamentioning
confidence: 99%